A Scoping review on the implementation of active recreational activities - Gula, Louie Petere (INSPIREE: Indonesian Sport Innovation Review, 2022)
The  purpose  of  the study. The aim of this study is to identify the prevalence of participants in physical activities, the motivation needed by the students to engage in the activity, challenges encountered by the implementors, health benefits, and recommendations and suggestions needed for the improvement of the implementation. Materials and methods. Using Arksey and O’Malley’s (2005) scoping review framework, a systematic analysis of the data of different articles was conducted. Results. It was found out that the implementation of active recreational activities offers different health benefits to the youth, physical literacy and orientation and motivation played a vital role in the implementation of the recreational activities. Conclusions. Therefore, the implementation of the active recreational activities must be strengthened in schools not just for the sake of participation but because they are motivated to. And the engagement of these activities must not only limit to school grounds but also engaged even at home and in the community.